Availability of essential medicines in Pakistan-A comprehensive document analysis. - Sunaina Rafi; Huma Rasheed; Muhammad Usman; Hafiz Awais Nawaz; Syed Muneeb Anjum; Mamoona Chaudhry; Zaheer-Ud-Din Babar (PLoS ONE)
Introduction Access to essential medicines (EMs) is a basic human right. Non-availability and shortages of EMs are reported for Pakistan but there is insufficient data to define the nature and magnitude of this problem. The current study is designed to systematically analyze the medicines included in the National Essential Medicines List (NEML) for their availability through comprehensive document analysis. Methods An expanded list of medicinal items was developed using the NEML of Pakistan (2018) to enlist individual medicines with their specifications. Registration status of the medicines was searched using three publicly accessible information sources; Pharmaguide 25th Edition, 2018-19, the on-line Drug Information System, and the Mobile Application Pharmapedia followed by a later 3-step validation of the data. The unregistered EMs were then further categorized into three subgroups in accordance with their possible remedial strategies. Findings The 19 studied categories comprised 690 EMs and it was found that 179 (26%) of these EMs don not have a registration status. However, it was also identified that the availability of 47 (26.2%) out of 179 unregistered EMs can be enssured by strengthening compounding services, and prioritizing registration of age-appropriate formulations. Availability of another 39 (21.7%) such medicines can be ensured by revising the NEML or the product registrations for the slight differences in their different specifications. The categories showing high proportion of unregistered medicines included anti-Parkinson's medicines (100%), antidotes and other substances used in poisoning (60%), diuretics (47%), anticonvulsants/antiepileptics (42%), hormones and other endocrine medicines and contraceptives (38%), medicines for mental and behavioral disorders (30%), anti-infectives (27%), medicines for pain and palliative care (26%), medicines for neonatal care (25%), medicines for diseases of joint (25%), gastrointestinal medicines (24%) and cardiovascular medicines (15%). Conclusion The study shows the absence of registration status of a significant number of EMs in Pakistan. This could be major barrier in their access. Strategies are needed to strengthen the processes of their registration on priority basis.